Death at the interface: Nanotechnology’s challenging frontier against microbial surface colonization - Kaur, Kiran Deep; Habimana, Olivier (Frontiers in Chemistry, 2022)
The emergence of antimicrobial-resistant bacterial strains has led to novel approaches for combating bacterial infections and surface contamination. More specifically, efforts in combining nanotechnology and biomimetics have led to the development of next-generation antimicrobial/ antifouling nanomaterials. While nature-inspired nanoscale topographies are known for minimizing bacterial attachment through surface energy and physicochemical features, few studies have investigated the combined inhibitory effects of such features in combination with chemical alterations of these surfaces. Studies describing surface alterations, such as quaternary ammonium compounds (QACs), have also gained attention due to their broad spectrum of inhibitory activity against bacterial cells. Similarly, antimicrobial peptides (AMPs) have exhibited their capacity to reduce bacterial viability. To maximize the functionality of modified surfaces, the integration of patterned surfaces and functionalized exteriors, achieved through physical and chemical surface alterations, have recently been explored as viable alternatives. Nonetheless, these modifications are prone to challenges that can reduce their efficacy considerably in the long term. Their effectiveness against a wider array of microbial cells is still a subject of investigation. This review article will explore and discuss the emerging trends in biomimetics and other antimicrobials while raising possible concerns about their limitations and discussing future implications regarding their potential combined applications (Figure 1).